Pengaruh Jenis dan Konsentrasi Zat Aditif Perekat dari Kulit Sapi pada Kayu Laminasi Jabon (Effect of Additive Substance and Concentration in Cowhide Adhesive on Jabon Laminated Wood) - Lukmanul H Zaini; Yusuf S Hadi; Mahdi Mubarak; Aris Sunaryo (Jurnal Ilmu dan Teknologi Kayu Tropis, 2017)
Recently, awareness of using natural adhesive materials for biocomposite products was increased. However, natural adhesive still facing many problems on physical and mechanical properties of the resulting biocomposite products. Therefore, adhesive modifications are needed in order to improve natural adhesives performance. The purpose of this study is to understand the effect of additive substance and concentration in cowhide adhesive on Jabon (Anthocephalus cadamba) laminated wood. Three types of additive substance (paraformaldehyde, polyurethane and albumin) were added into cowhide adhesive with three different concentration (10, 20 and 30%). The testing were conducted on moisture content, density, shear strength, and delamination. Shear strength was tested according to ASTM D-905 while moisture content, density, and delamination were tested according to JAS 234:2003 standard for Glue Laminated Timber. The results showed that all treatment were not affecting moisture content and density. In addition, additive substance was affecting shear strength and delamination. Nonetheless, concentration of additive substance was only affecting shear strength. The best shear strength value were 63.75 kg cm-2. The value meets the JAS 234:2003 standard. Compared to all of the treatment applied, the best result was achieved by 30% paraformaldehyde addition. Based on this experiment, laminated wood is suitable for interior application.Keywords: bio-adhesive, cowhide adhesive, jabon, laminated wood